(untitled) (INCH : Journal of Infant and Child Healthcare, 2022)
The results of the 2018 Basic Health Research (Riskesdas) show that the percentage of toddler stunting in Riau Province is currently 27.35% spread over 12 districts/cities. Kampar Regency is one of the regencies in Riau Province that has a stunting locus village in 2019, with a prevalence of 32.05%. This prevalence is above provincial and national prevalence. The purpose of this study was to determine the description of maternal height and toddler stunting in Petapahan Village, Kampar Regency, Riau. This research is descriptive with the type of cross sectional research. The results of this study show that there are 15 mothers who have short height and 35 people who have normal height. There were 34 stunting toddlers who were male and 16 female. Mothers with short height who have stunting toddlers are 15 people and mothers with normal height who have stunting toddlers are 35 people